Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/smtd.202300038
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Steric Link to Copper Precursor Decomposition: A Multi‐Faceted Study for the Printing of Flexible Electronics

Abstract: The field of printed electronics strives for lower processing temperatures to move toward flexible substrates that have vast potential: from wearable medical devices to animal tagging. Typically, ink formulations are optimized using mass screening and elimination of failures; as such, there are no comprehensive studies on the fundamental chemistry at play. Herein, findings which describe the steric link to decomposition profile: combining density functional theory, crystallography, thermal decomposition, mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As such, combinations of copper metal and paper as the substrate could be an excellent combination of materials to consider as environmental impact, sustainability, and recyclability become more of a focus. In this regard, Knapp has recently demonstrated that a copper-based MOD ink can be thermally decomposed at temperatures as low as 150 °C to produce functional conductive traces on paper …”
Section: Substrates and Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, combinations of copper metal and paper as the substrate could be an excellent combination of materials to consider as environmental impact, sustainability, and recyclability become more of a focus. In this regard, Knapp has recently demonstrated that a copper-based MOD ink can be thermally decomposed at temperatures as low as 150 °C to produce functional conductive traces on paper …”
Section: Substrates and Coatingsmentioning
confidence: 99%
“…In this regard, Knapp has recently demonstrated that a copper-based MOD ink can be thermally decomposed at temperatures as low as 150 °C to produce functional conductive traces on paper. 40 4.3. Substrate Coatings and Treatments.…”
Section: Substrates and Coatingsmentioning
confidence: 99%